2016
DOI: 10.5539/ies.v9n12p61
|View full text |Cite
|
Sign up to set email alerts
|

Universal Beliefs and Specific Practices: Students’ Math Self-Efficacy and Related Factors in the United States and China

Abstract: This study intends to compare and contrast student and school factors that are associated with students' mathematics self-efficacy in the United States and China. Using hierarchical linear regressions to analyze the Programme for International Student Assessment (PISA) 2012 data, this study compares math self-efficacy, achievement, and variables such as math teacher support and socioeconomic status (SES) between 15-year-old students in the U.S. and in Shanghai, China. The findings suggest that on average, stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 21 publications
0
10
0
2
Order By: Relevance
“…All findings of the studies showed that the lower the secondary school students' mathematics self-efficacy, the lower the marks (performance) of mathematics results they scored. Usually, the studies showed that students' mathematics self-efficacy with some other factors such as mathematics anxiety (Aksu, Ozkaya, Gedik & Konyalıoglu, 2016;O'Keeffe, White, Panizzon, Elliott, & Semmens, 2018;Reyes, 2019a;Reyes, 2019b;Recber, Isikal & Koc, 2018;Yuksel & Geban, 2016), teacher support (Wu, 2016;Yildirim & Yildirim, 2019), online learning (Ichinose & Bonsangue, 2016;Parsons & Gonzalez, 2018), program (Cleary, Velardi & Schnaidman, 2017;Snipes, Huang, Jaquet & Finkelstein, 2016), learning materials (Cai, Liu, Yang & Liang, 2019;Peranginangin, Saragih & Siagian, 2019;Ulandari, Amry & Saragih 2019), instructional games (Reyes, 2019b), and discovery learning (Simamora, Saragih & Siregar, 2019) influenced the secondary school students' performance in mathematics. Hence, the students that have high performance in mathematics were the students' that have high mathematics selfefficacy and vice versa.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All findings of the studies showed that the lower the secondary school students' mathematics self-efficacy, the lower the marks (performance) of mathematics results they scored. Usually, the studies showed that students' mathematics self-efficacy with some other factors such as mathematics anxiety (Aksu, Ozkaya, Gedik & Konyalıoglu, 2016;O'Keeffe, White, Panizzon, Elliott, & Semmens, 2018;Reyes, 2019a;Reyes, 2019b;Recber, Isikal & Koc, 2018;Yuksel & Geban, 2016), teacher support (Wu, 2016;Yildirim & Yildirim, 2019), online learning (Ichinose & Bonsangue, 2016;Parsons & Gonzalez, 2018), program (Cleary, Velardi & Schnaidman, 2017;Snipes, Huang, Jaquet & Finkelstein, 2016), learning materials (Cai, Liu, Yang & Liang, 2019;Peranginangin, Saragih & Siagian, 2019;Ulandari, Amry & Saragih 2019), instructional games (Reyes, 2019b), and discovery learning (Simamora, Saragih & Siregar, 2019) influenced the secondary school students' performance in mathematics. Hence, the students that have high performance in mathematics were the students' that have high mathematics selfefficacy and vice versa.…”
Section: Methodsmentioning
confidence: 99%
“…There are only 2 out of 26 studies that investigated the influence of teacher support as the factor affecting the secondary school students' mathematics self-efficacy. The two studies were conducted by Wu (2016) and Yildrim & Yildrim (2019). There is a positive correlation between the teacher support and secondary school students' mathematics self-efficacy.…”
Section: The Factors That Can Influence Secondary School Students' Mathematics Self-efficacymentioning
confidence: 99%
“…Efficacious individuals outperform their counterparts who are not (Cave, Evans, Dewey, & Hartshorn, 2018). Students with high self-efficacy are likely to overcome difficult tasks than those with low self-efficacy (Martin & Rimm-Kaufman, 2015;Wu, 2016). While efficacious students make an effort to achieve their set goals, those who are not dwell on their shortcomings at school and makes little effort to achieve their set goals (Bandura, 1978;Corkett, Hatt, & Benevides, 2011;Wang, Harrison, Cardullo, & Lin, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…One significant predictor of high academic achievement at the university level is self-efficacy (Bartimote-Aufflicka, Bridgeman, Walker, Sharma, & Smith, 2016;Schunk, Meece, & Pintrich, 2013). Self-efficacy is directly related to the success of students (Chao, McInerney, & Bai, 2019;Corkett, Hatt, & Benevides, 2011;Wu, 2016). English self-efficacy is "an individual's belief or confidence in his/her ability to use English language to communicate with others, understand English conversations, read materials, and write in English" (Wang, Harrison, Cardullo, & Lin, 2018, p. 235).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kemahiran berfikir, sikap, jantina, kepercayaan diri dan keyakinan diri merupakan pemboleh ubah yang boleh dikaitkan dengan faktor dalaman, manakala status sosio-ekonomi dan kaedah pembelajaran menunjukkan faktor persekitaran yang dikaji bersama dengan efikasi kendiri pelajar. Terdapat juga faktor guru ditemui dalam analisis ini seperti sokongan guru (King-Sears & Strogilos, 2020;Usta, 2016;Wu, 2016), efikasi kendiri guru (Chang, 2015;Sarac, 2017) dan kebolehan guru mengajar matematik (Kaskens et al, 2020;King-Sears & Strogilos, 2020;Regier & Savic, 2020).…”
Section: Trend Pembolehubah Perkaitanunclassified